The Spiritual Well-Being to the Quality of Life of Heart Failure Patients - Hudiyawati, Dian; Chouhan, Devraj Singh; Wibowo, Della Mardiana; Mujannidah, Afidatul (Jurnal Berita Ilmu Keperawatan, 2024)
Heart failure is caused by the heart being unable to maintain normal blood flow. Some patients with heart failure expressed that they needed nurses' help with their physical, psychological, and spiritual problems. Spiritual Well-Being and its components play an important role in a person's declining quality of life and have been linked to various other health factors. This research aims to determine the relationship between spiritual well-being and the quality of life of heart failure patients. The sample for this research was 100 respondents taken using the accidental sampling technique. Data analysis uses the chi-square correlation test if the test conditions are met. If the test requirements are not met, use the alternative Fisher exact test. The instruments used in this research were the Spiritual Needs Questionnaire (SpNQ) and the Minnesota Living with Heart Failure Questionnaire (MLHFQ). The results of this study illustrate that there is no relationship between quality of life scores and all aspects of the spiritual needs of heart failure patients (p> 0.05). The results of the analysis carried out showed that NYHA functional status (p= 0.044) and ejection fraction (r= -0.205, p= 0.041) influenced the spiritual needs of heart failure patients. The results of this study indicate that the patient's spiritual needs are not related to the general quality of life score, but have a significant relationship with the physiological dimensions of quality of life, ejection fraction, and NYHA functional status.